PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF SISWA SMP NEGERI 3 JONGGAT TAHUN PELAJARAN 2016/2017 - Dewi Hardiyanti; Siti Nurhidayati; Ismail Efendi (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract: The purpose of this research is to know the effect of Learning Problem Based Learning Model to cognitive learning outcomes of students of class VIII SMPN 3 Jonggat Student Year 2016 / 2017. Type of research used in this study is Quasi Eksperimen.Rancangan research in this research is Only Post- test Control Goup Design and research sample that is class VIII A of 23 people as experimental class and class VIII B as many as 23 people as control class using observation sheet to know the result of cognitive learning. Technique of data analysis using T-test, from result Test of research hypothesis got result of calculation of post-test for titung equal to 8,85 and ttable value equal to 2,042 with error level 5% and dk = n1 + n2- 2 = 18 + 19 - 2 = 35 ie amounted to 2.042. So from the results of the calculation seen t count> ttable 8.85> 2.042 which means Ha accepted and Ho rejected so that it can be said that there is influence of learning model Problem Based Learning on student cognitive learning outcomes.